2010
DOI: 10.1586/ers.10.57
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in asthma pathophysiology and immunopathology?

Abstract: Research on asthma pathophysiology over the past decade has expanded the complex repertoire involved in the pathophysiology of asthma to include inflammatory, immune and structural cells, as well as a wide range of mediators. Studies have identified a role for connective and other mesenchymal tissues involved in airway remodeling. Recent findings have implicated the innate immune response in asthma and have revealed interesting patterns of interaction between the innate and adaptive immune response and the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 344 publications
0
21
0
2
Order By: Relevance
“…Because Th 2 cytokines such as those quantified in this study are related to recruitment of mast cells, maturation of eosinophils, IgE synthesis and cell mobilization in allergic asthma [29], and considering that elevated levels of inosine are found at inflamed sites [4,32], we have inferred possible auto-control of allergic lung inflammation that might be mediated by purines, however, through a mechanism that seems to be independent of A 2A or A 2B receptor activation, since ZM241385 and alloxazine did not interfere with the effects of inosine on IL-4 and IL-5 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Th 2 cytokines such as those quantified in this study are related to recruitment of mast cells, maturation of eosinophils, IgE synthesis and cell mobilization in allergic asthma [29], and considering that elevated levels of inosine are found at inflamed sites [4,32], we have inferred possible auto-control of allergic lung inflammation that might be mediated by purines, however, through a mechanism that seems to be independent of A 2A or A 2B receptor activation, since ZM241385 and alloxazine did not interfere with the effects of inosine on IL-4 and IL-5 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The research on asthma over the past decade has expanded the complex repertoire involved in its The difference between groups was determined by ANOVA followed by Newman-Keuls multiple comparison test *P<0.001 when compared to basal group pathophysiology to include inflammatory, immune and structural cells as well as a wide range of mediators [29]. Some studies have been shown that adenosine is a proinflammatory mediator involved in the pathogenesis of asthma [7], since recent research have demonstrated that elevated levels of adenosine induces bronchoconstriction and was found in the airways of patients with asthma [7,30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this model has great potential for research into airway remodeling associated with asthma. [57][58][59] That these cell types alone can create an intact matrix merits further investigation into the genesis and progression of matrix formation in the lung, and the importance of their interactions with other cell types in this process. It is also worth noting that the discovery of the potential of PFs and SMCs alone to generate the extracellular matrix would not have been possible in 2D, since in 2D stains, positive collagen type I and laminin stains localized around the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The long-held view of asthma as a quintessential chronic allergic disease (3,4) accompanied by eosinophil-mediated airway inflammation linked with increased levels of T-helper cell type 2 (Th2)-derived cytokines is being reinterpreted in light of the realization that the underlying immune responses in these patients are much more diverse (reviewed in References 2,[5][6][7][8]. Moreover, eosinophil targeting therapies have been efficacious only in a narrow subgroup of eosinophilic asthma patients with lower use of steroids and decreased exacerbation events as the most significant end point measures (9)(10)(11)(12).…”
mentioning
confidence: 99%